Influência dos métodos manuais de polinização e da proximidade de vegetação nativa na produção do macujá-amarelo (Passiflora edulis f. flavicarpa Deneger, Passifloraceae) no Nordeste do Brasil - SILVA, Sandra Rodrigues da (2016)
The agriculture expansion results in the suppression of areas of native vegetation, creating areas of native vegetation fragmented, affecting resource availability and isolating plant and animal populations in Brazil and the world's ecosystems. One result of such expansion is to reduce pollinator populations, which play an important functional role in natural ecosystems and managed, such as agricultural crops. The yellow passion fruit (Passiflora edulis f. Flavicarpa., Passifloraceae) cultivation target of this study, is an agricultural culture dependent on cross-pollination and large bees (Xylocopa spp.) For the production of fruit. These bees have solitary habit and nest in tree trunks, stressing the importance of conservation of native vegetation areas to maintain their populations. Several studies indicate that proximity of native vegetation areas favors pollination and production of agricultural crops, for serving as a suitable habitat for pollinators. However, little is known about it in relation to the yellow passion fruit. With the low frequency Xylocopa genre of bees has been observed in the areas of the yellow passion fruit cultivation, farmers need to replace the process of natural pollination by hand pollination, which can be made with pollen of the day or stored, resulting in high costs for production. The aim of this study was to determine whether there is influence of the distance of the native vegetation in relation to areas of cultivation of passion fruit on the pollination and production at different times of the year, and to investigate the effectiveness of different manual pollination methods in production. The study was conducted in the Irrigated Perimeter of Maniçoba in Juazeiro- BA in eight areas of passion fruit crops with different distances from a native area of caatinga type in the dry and wet seasons of 2014 and 2015. The frequency of visits , the number, morphology, weight, the amount of pulp and fruit brix areas were compared. For manual pollination experiment were tested cross-pollination methods directed to the pollen day and pollen stored for 24 hours at an average temperature of 4-6 ° C, using gloved fingers, fingers without gloves, body and natural bee pollination. Furthermore, the viability was verified in vitro pollen germination and pollen tube growth in the stigma. Data were analyzed using the Tukey test, chi-square, ANOVA and Pearson's correlation test. Our results indicate that the distance alone did not affect fruit production, but when we include the season in the analysis, there was influence both the frequency of pollinators as the quantity and quality of fruits formed. In the dry, the nearest crop areas of native vegetation receive more frequent visits and produce larger fruit and higher quality. This season there was greater frequency of pollinators, quantity and quality of the fruit compared with the rainy season, indicating a more profitable production period and lower cost of hand labor for the producer. As for the directed pollination methods, the control showed the best quality fruits and method using the body of the bee had a higher fruit set. Treatment gloved fingers had the worst fruit. The day of pollen showed higher viability when the anthers were stored separately from the rest of the flower, and in-vitro germination of pollen showed greater success when the flower was fully stored. The higher the lowest pollen storage time is viability. Flowers pollinated with pollen stored did not form fruits, conversely to that observed for those pollinated with pollen of the day. Our results show the importance of natural pollination by bees Xylocopa gender in passion fruit crops, and the relevance of native vegetation for production, especially in the dry. So the natural pollination method seems to provide a good fruit quality and reduce labor costs for producers of this crop.